Of the just war - Monsalve Solórzano, Alfonso (Estudios de Filosofía, 2004)
This paper presents a synthesis of normative theories on just war, showing the theorical consensus about the three categories of ius ad bellum O’ustice of war), ius in bello (justice in war) and ius postbellum (justice post-war). Then, these concepts are developed for the case of a real war.